Interface Engineering of Flexible Piezoresistive Sensors via Near‐Field Electrospinning Processed Spacer Layers. Issue 4 (29th January 2021) - Huang, Yan; You, Xiangyu; Tang, Zhiqiang; Tong, Kai‐Yu; Guo, Ping; Zhao, Ni
Abstract: The interface contact between the active material and its neighboring metal electrodes dominates the sensing response of mainstream high‐sensitivity piezoresistive pressure sensors. However, the properties of such interface are often difficult to control and preserve owing to the limited strategies to precisely engineer the surface structure and mechanical property of the active material. Here, a top‐down fabrication method to create a grid‐like polyurethane fiber‐based spacer layer at the interface between a piezoresistive layer and its contact electrodes is proposed. The tuning of the period and thickness of the spacer layer is conveniently achieved by a programmable near‐field electrospinning process, and the influence of the spacer structure on the sensing performance is systematically investigated. The sensor with the optimized spacer layer shows a widened sensing range (230 kPa) while maintaining a high sensitivity (1.91 kPa −1 ). Furthermore, the output current fluctuation of the sensors during a 74 000‐cycle test is drastically reduced from 14.28% (without a spacer) to 3.63% (with a spacer), demonstrating greatly enhanced long‐term reliability. The new near‐field electrospinning‐based strategy is capable of tuning sensor responses without changing the active material, providing a universal and scalable path to engineer the performances of contact‐dominant sensors. Abstract : A top‐down fabrication method is proposed to well control the interface between electrodes and the piezoresistive material of pressure sensors by the addition of a grid‐like polyurethane fiber‐based spacer layer. The period and the thickness of the near‐field electrospinning processed spacer layer are tuned to investigate their influences on the sensing performance.